Vaccines for TB: Lessons from the Past Translating into Future Potentials - Gee Jun Tye; Min Han Lew; Yee Siew Choong; Theam Soon Lim; Maria Elena Sarmiento; Armando Acosta; Mohd Nor Norazmi (Journal of Immunology Research)
Development of vaccines for infectious diseases has come a long way with recent advancements in adjuvant developments and discovery of new antigens that are capable of eliciting strong immunological responses for sterile eradication of disease. Tuberculosis (TB) that kills nearly 2 million of the population every year is also one of the highlights of the recent developments. The availability or not of diagnostic methods for infection has implications for the control of the disease by the health systems but is not related to the immune surveillance, a phenomenon derived from the interaction between the bacteria and their host. Here, we will review the immunology of TB and current vaccine candidates for TB. Current strategies of developing new vaccines against TB will also be reviewed in order to further discuss new insights into immunotherapeutic approaches involving adjuvant and antigens combinations that might be of potential for the control of TB.